Jakość w medycyniePaternalism in medicine - Wroński, Konrad; Cywiński, Jarosław; Bocian, Roman; Dziki, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Paternalism is part of traditional medicine. Paternalism represents in medicine an authoritarian approach to patients. In this model the doctor decides what kind of treatment is best for the patient. Patient autonomy is very limited or non-existent. In medicine, discussion on the subject of relinquishment of the doctor’s paternalistic approach to the patient appeared in the second half of the 20th century. In the 1980s in medical literature there was a wave of criticism of medical paternalism. The new and at present valid model is the model based on doctor-patient partnership, in which the patient has considerable autonomy and alone makes the decision about method of treatment. In the new system the doctor is an adviser whose task is to introduce all possible methods of treatment and to help to choose the best one. However, the final decision of method of treatment is left for the patient.